Becoming a Scientist: Views of Few Scientists - M. Karakas (University of Sofia, 2018)
This study examined experiences of science faculty who teach introductory undergraduate science courses including the fields of chemistry, biology, physics, and earth science. Participants were seventeen science instructors from five different institutions in the northeastern U.S. and all of them were interviewed. Findings revealed that participants generally had a public schooling experience. Their interest in science generally started as self-motivated and self-interest in middle and high school years, except for the three female scientists who got interested in science in their college years. Their parents were generally college graduates and supported them in their education in general, but did not give them any particular guidance in getting into their field of sci-ence. Most of the participants described their best science teachers as being, enthusiastic and exciting about their subject, motivating and involved with their students, and as a person who uses a lot of demonstrations and hands-on experiments. The participants were interested with general social issues in science, such as evolution vs. creationism and stem cell controversy. The majority of the scientists said that they understood how science really works in gradu-ate or after graduate school.